Efficacy and safety of low-dose colchicine in patients with coronary disease: a systematic review and meta-analysis of randomized trials. (26th March 2021) - Fiolet, Aernoud T L; Opstal, Tjerk S J; Mosterd, Arend; Eikelboom, John W; Jolly, Sanjit S; Keech, Anthony C; Kelly, Peter; Tong, David C; Layland, Jamie; Nidorf, Stefan M; Thompson, Peter L; Budgeon, Charley; et al.
Abstract: Aims: Recent randomized trials demonstrated a benefit of low-dose colchicine added to guideline-based treatment in patients with recent myocardial infarction or chronic coronary disease. We performed a systematic review and meta-analysis to obtain best estimates of the effects of colchicine on major adverse cardiovascular events (MACE). Methods and results: We searched the literature for randomized clinical trials of long-term colchicine in patients with atherosclerosis published up to 1 September 2020. The primary efficacy endpoint was MACE, the composite of myocardial infarction, stroke, or cardiovascular death. We combined the results of five trials that included 11 816 patients. The primary endpoint occurred in 578 patients. Colchicine reduced the risk for the primary endpoint by 25% [relative risk (RR) 0.75, 95% confidence interval (CI) 0.61–0.92; P  = 0.005], myocardial infarction by 22% (RR 0.78, 95% CI 0.64–0.94; P  = 0.010), stroke by 46% (RR 0.54, 95% CI 0.34–0.86; P  = 0.009), and coronary revascularization by 23% (RR 0.77, 95% CI 0.66–0.90; P  < 0.001). We observed no difference in all-cause death (RR 1.08, 95% CI 0.71–1.62; P  = 0.73), with a lower incidence of cardiovascular death (RR 0.82, 95% CI 0.55–1.23; P  = 0.34) counterbalanced by a higher incidence of non-cardiovascular death (RR 1.38, 95% CI 0.99–1.92; P  = 0.060). Conclusion: Our meta-analysis indicates that low-dose colchicine reduced the risk of MACE as well as that of myocardial infarction, stroke, and the need for coronary revascularization in a broad spectrum of patients with coronary disease. There was no difference in all-cause mortality and fewer cardiovascular deaths were counterbalanced by more non-cardiovascular deaths. Graphical Abstract: